The Bph45 gene confers resistance against brown planthopper in rice by reducing the production of limonene - Li, Charng-Pei; Wu, Dong-Hong; Huang, Shou-Horng; Meng, Menghsiao; Shih, Hsien-Tzung; Lai, Ming-Hsin; Chen, Liang-Jwu; Jena, Kshirod K.; Hechanova, Sherry Lou; Ke, Ting-Jyun; Chiu, Tai-Yuan; Tsai, Zong-Yuan; et al. (MDPI, 2023)
Brown planthopper (BPH), a monophagous phloem feeder, consumes a large amount of photoassimilates in rice and causes wilting. A near-isogenic line ‘TNG71-Bph45’ was developed from the Oryza sativa japonica variety ‘Tainung 71 (TNG71) carrying a dominant BPH-resistance locus derived from Oryza nivara (IRGC 102165) near the centromere of chromosome 4. We compared the NIL (TNG71-Bph45) and the recurrent parent to explore how the Bph45 gene confers BPH resistance. We found that TNG71-Bph45 is less attractive to BPH at least partially because it produces less limonene. Chiral analysis revealed that the major form of limonene in both rice lines was the L-form. However, both L- and D-limonene attracted BPH when applied exogenously to TNG71-Bph45 rice. The transcript amounts of limonene synthase were significantly higher in TNG71 than in TNG71-Bph45 and were induced by BPH infestation only in the former. Introgression of the Bph45 gene into another japonica variety, Tainan 11, also resulted in a low limonene content. Moreover, several dominantly acting BPH resistance genes introduced into the BPH-sensitive IR24 line compromised its limonene-producing ability and concurrently decreased its attractiveness to BPH. These observations suggest that reducing limonene production may be a common resistance strategy against BPH in rice.